ปัจจัยที่ส่งผลต่อค่าใช้จ่ายในการรักษาสุขภาพประเภทการเจ็บป่วยของผู้ป่วยนอก - แซ่ตั๊น จุฑาทิพย์; สอนสมนึก สุภาพร; สินสมบูรณ์ทอง สายชล (Thai Journal of Science and Technology, 2021)
This research aimed to identify factors affecting outpatient healthcare expenditure and create a multiple linear regression model for predicting outpatient healthcare expenditure. The studied dependent and independent variables were secondary data on health and welfare survey 2017 from Thailand’s National Statistical Office. The sample size is 384 people, calculated by Cochran’s sample size formula in case of an unknown proportion of the population and simple random sampling without replacement. There are 35 independent variables, which are selected by using Enter Regression. The results of the study revealed that there are 8 independent variables which affect outpatient healthcare expenditure such as age (X5), primary school (X6_1), single status (X7_1), marital status (X7_2), public hospital (X15_1), private hospital (X15_2), health insurance with the insurance company (X16_4) and travel expenses (X17). All independent variables combined can predict outpatient healthcare expenditure by 56.9 percent. The prediction model is = (3.452 + 0.014X5 + 0.605X6_1 + 1.246X7_1 + 0.983X7_2 + 3.427X15_1 + 2.810X15_2 + 1.982X16_4 + 0.001X17).